Analisis Laporan Keuangan dalam Menilai Kinerja Keuangan pada PT Indocemen Tunggal Prakarsa Tbk Periode 2010-2024 - Ramadani, Bintang; Puji Muniarty (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the financial performance of PT Indocement Tunggal Prakarsa Tbk for the period 2010–2024 based on the company's financial statements. The method used in this study is descriptive with a financial ratio analysis approach, covering liquidity, solvency, profitability, and activity ratios. The data used is secondary data in the form of the company's annual financial reports obtained from the Indonesia Stock Exchange and the company's official website. The results show that the company's financial performance fluctuates from year to year. The liquidity ratio indicates a relatively good condition in meeting short-term obligations. The solvency ratio indicates the company's ability to manage debt effectively. Meanwhile, the profitability and activity ratios show increases and decreases over certain periods influenced by economic and industry conditions.